Analysis of the Appropriateness of Human Resource Management and Infrastructure: Synergy and Efficiency in School Institution Development - Muhammad, Mutsanna Bin; Rondo, Muhammad Raihan (Proceeding International Conference on Religion, Science and Education, 2025)
In an increasingly complex and competitive educational environment, there is a challenge in creating effective synergy between human resource management and infrastructure. External variables such as education policy, student needs and community dynamics can affect the fit. This study aims to analyze the compatibility between human resource management (HRM) and infrastructure in the context of school institutional development, using a literature review approach. The results of the analysis show that a good synergy between human resource management and infrastructure in school institutions can improve the quality of education. Effective HR management and adequate infrastructure create a conducive learning environment, improve teacher performance and student and staff satisfaction. This research can provide insights for practitioners and academics in formulating more effective strategies to integrate HRM and infrastructure management in achieving better results.